Czy publiczność podpali teatr? Fenomen Indignados wobec kryzysu legitymizacji i modelu demokracji deliberatywnej - Kurdelski, Hubert (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2017)
This article presents the history and the development of tthe Spanish “Indignant” movement in the long term, i.e. from the occupation of Puerta del Sol to this day. The paper discusses social functions carried out by collectives constituting the above-mentioned movement. The main focus is put on the analysis of civic groups’ influence on solving problems connected with the crisis of the Spanish state and on the political and legal system of this country. The condition of Spanish state institutions (being an the example of contemporary European democratic system) is considered from the perspective of the legitimization of its resolutions and citizens’ participation in making key decisions. The analysis aims at describing the place of the “Indignados” in Spanish political life and forecasting the directions of the movement’s development. The model of eliberative democracy by Jürgen Habermas is used in the course of the work. The selection of information and the analysis of the Indignants’ actions are based on media reports and participant observations made by the author who during the last three years has participated in the actions of the movement in Sevilla, Alicante and Saragossa.